DAYA ANTIBAKTERI EKSTRAK TERIPANG PASIR (Holothuria scabra) TERHADAP PERTUMBUHAN BAKTERI (Salmonella typhi) SECARA IN VITRO - Feffiana M Amin; Dessy Yoswaty; Irvina Nurrachmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
Sea cucumbers are ones among the marine resources in Indonesian, among its group was sandfish (Holothuria scabra). Sandfish has potential as a new biopharmaceutical material due to very rich in secondary metabolites and also has a potential as an antibacterial. Salmonella typhi is pathogenic bacteria that can cause disease in humans. The purpose of the research was to determine on how much the ability of antibacterial inhibiton which have sandfish for S. typhi bacteria and then for knowing the bioactive compounds. The result showed that the sandfish extract has the ability to inhibit the growth of S. typhi bacteria. The ability of sandfish extract inhibitory is classified as a moderate range, i.e. 5 – 10 mm. Furthermore based on the result of phytochemical screening test, the compound has capable of inhibiting the growth of S. typhi bacteria were include alkaloids, saponins, steroids, and triterpenoids.Keywords : H. scabra, antibacterial, Salmonella typhi, bioactive.